Factor H Is Bound by Outer Membrane-Displayed Carbohydrate Metabolism Enzymes of Extraintestinal Pathogenic Escherichia coli and Contributes to Opsonophagocytosis Resistance in Bacteria - Sun, Yu; Xu, Bin; Zhuge, Xiangkai; Tang, Fang; Wang, Xuhang; Gong, Qianwen; Chen, Rui; Xue, Feng; Dai, Jianjun (Frontiers in Cellular and Infection Microbiology, 2021)
Extraintestinal pathogenic Escherichia coli (ExPEC) causes bloodstream infections in humans and animals. Complement escape is a prerequisite for bacteria to survive in the bloodstream. Factor H (FH) is an important regulatory protein of the complement system. In this study, ExPEC was found to bind FH from serum. However, the mechanisms of ExPEC binding to FH and then resistance to complement-mediated attacks remain unclear. Here, a method that combined desthiobiotin pull-down and liquid chromatography-tandem mass spectrometry was used to identify the FH-binding membrane proteins of ExPEC. Seven identified proteins, which all were carbohydrate metabolic enzymes (CMEs), including acetate kinase, fructose-bisphosphate aldolase, fumarate reductase flavoprotein subunit, L-lactate dehydrogenase, dihydrolipoamide dehydrogenase, phosphoenolpyruvate synthase, and pyruvate dehydrogenase, were verified to recruit FH from serum using GST pull-down and ELISA plate binding assay. The ELISA plate binding assay determined that these seven proteins bind to FH in a dose-dependent manner. Magnetic beads coupled with any one of seven proteins significantly reduced the FH recruitment of ExPEC (p < 0.05). Subsequently, immunofluorescence and colony blotting determined that these seven CMEs were located on the outer membrane of ExPEC. Furthermore, the FH recruitment levels and C3b deposition levels on bacteria were significantly increased and decreased in an FH-concentration-dependent manner, respectively (p < 0.05). The FH recruitment significantly enhanced the ability of ExPEC to resist the opsonophagocytosis of human macrophage THP-1 in an FH-concentration-dependent manner (p < 0.05), which reveals a new mechanism for ExPEC to escape complement-mediated killing. The identification of novel outer membrane-displayed CMEs which play a role in the FH recruitment contributed to the elucidation of the molecular mechanism of ExPEC pathogenicity.